Landslide Hazard-Prevention in Balakot Region, Pakistan - Abdul Salam Soomro; Abdul Qadeer Khan Rajput; Sarfraz Hussain Solangi (Mehran University Research Journal of Engineering and Technology, 2012)
The earthquake triggered enormous landslides on 8th October 2005 in the various areas of Pakistan especially in Balakot Region. This research paper fulfilled the urge to develop alternative landslide planning based on the consideration of landslide preventing measures using GIS (Geographical Informaton Systems) techniques. This specific type of land use planning differs from traditional type of land use planning due to consideration of the probable hazard of landslide disaster by applying zonation methodology for finding the appropriate suitable areas for various development purposes. The various parameters e.g. elevation, slope angle, forest/ vegetations, faults, landslide zones, and rainfall were utilized as GIS data themes in the vector format. The different GIS techniques were used: (i) Clipping the data layers; (ii) Spatial analysis by converting the vector layers into raster format; (iii) Classification of data themes into certain classes; (iv) Overlaying the data themes and (v) Map calculation techniques through GIS standard software. This applied research has found that various different regions such as high suitable, moderate suitable, low suitable and unsuitable may be considered as preventive measures from the probable hazard of the landslide disaster in future for rehabilitation and redevelopment purpose which can save human lives, residential and commercial infrastructure in future. It is believed that the various predicted regions for preventing landslide hazards can be very beneficial to the decision makers for the redevelopment of the region in future.